Biosimilars in dermatology - Mazur, Małgorzata; Olek-Hrab, Karolina; Karczewski, Jacek; Teresiak-Mikołajczak, Ewa; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Over the last decade the availability of biological drugs for the treatment of psoriasis vulgaris, psoriatic arthritis and many other inflammatory diseases has revolutionized the treatment of these diseases around the world. Due to the high cost of therapy, the search has started for biosimilars. In dermatology the greatest interest in biosimilar medicines concerns inhibitors of tumor necrosis factor a (TNF-α, for use in the treatment of psoriasis vulgaris and psoriatic arthritis (infliximab, etanercept, adalimumab). The most important element of the safety of biologicals is their immunogenicity. Therefore, when discussing biosimilars, attention needs to be paid to the dangers of their immune activity. In view of the fact that the drugs contain and aggregates, produced by living organisms or cultures of living cells, they cannot be compared in any way to low molecular weight synthetic generics (called generics). Biosimilars are authorized for use in patients and treated as equivalent to the reference medicine only after passing a number of studies and assessments. As it is well known, the development of medicine and pharmacology is extremely intense, and the market in biological medicine is developing much faster than that of all other drugs, which underlines their important role in modern medicine. Currently, the subject of biosimilars is one of the most important challenges and topics of discussion around the world, including pharmacovigilance and legal and economic regulatory standards. It seems inevitable that biosimilar products will be introduced for the treatment of diseases with indications corresponding to the original product on which they are based.